2019
DOI: 10.1002/adom.201900039
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free and Morphology‐Controlled Growth of 2D Perovskite Nanowires for Polarized Light Detection

Abstract: Ruddleson–Popper (RP) perovskites have emerged as a class of material inheriting the superior optoelectronic properties of two materials: perovskites and 2D materials. The large exciton binding energy and natural quantum well structure not only make these materials ideal platforms to study light–matter interactions but also render them suitable for fabrication of various functional optoelectronic devices. Nanoscale structuring and morphology control have led to semiconductors with enhanced functionalities. Nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…These characteristics strongly recommend the organic–inorganic hybrid perovskites as ideal building blocks for high‐performance PDs. Perovskites with different structures (polycrystalline film,9 single crystal,10 and low‐dimensional nanostructure59)have been synthesized. Together with various device configurations, perovskites‐based devices demonstrate unprecedented progress in photodetecting performance 60.…”
Section: Materials For Heterojunction Uv Pdsmentioning
confidence: 99%
“…These characteristics strongly recommend the organic–inorganic hybrid perovskites as ideal building blocks for high‐performance PDs. Perovskites with different structures (polycrystalline film,9 single crystal,10 and low‐dimensional nanostructure59)have been synthesized. Together with various device configurations, perovskites‐based devices demonstrate unprecedented progress in photodetecting performance 60.…”
Section: Materials For Heterojunction Uv Pdsmentioning
confidence: 99%
“…[25] Subsequently, linearly polarized luminescence based on HPs NCs, [26] NWs, [27,28] NPLs, [29,30] NRs, [31] composites, [32][33][34][35][36][37][38] and highly oriented film [39] were sequentially reported. Meanwhile, linearly polarized light detection was also being implemented in HPs-based single crystals, [40] NWs, [4,41,42] and NPLs. [30] In particular, in 2019, Peng et al [43] first reported a detector based on 2D HPs bulk photovoltaic effect (BPVE), realizing high sensitive detection of linearly polarized light.…”
Section: While Halide Perovskites (Hps) Have Achieved Enormous Succesmentioning
confidence: 99%
“…In addition to 3D cubic perovskite we just mentioned, 2D perovskite is another perovskite family that possesses good polarization property because of its asymmetric layered crystal structure. For example, Ghoshal et al demonstrated a high DOLP of 0.73 from an individual (BA) 2 PbI 4 NW,43 and Ma et al reported polarized PL based on a group of chiral (MBA) 2 PbI 4 microplates with a DOLP of 0.176 44. Compared with perovskite‐based devices in the literature, the printed perovskite NW arrays in this study present the highest DOLP of 0.84, suggesting its potential for polarized light application.…”
Section: Resultsmentioning
confidence: 99%